Macroeconomic expectations of households amd professional forecasters - Christopher D. Carroll (The Johns Hopkins University, Department of Economics, 2002)
Economists have long emphasized the importance of expectations in determining macroeconomic outcomes Yet there has been almost no recent effort to model actual empirical expectations data; instead macroeconomists usually simply assume expectations are rational This paper shows that while empirical household expectations are not rational in the usual sense expectational dynamics are well captured by a model in which households' views derive from news reports of the views of professional forecasters which in turn may be rational The model's estimates imply that people only occasionally pay attention to news reports; this inattention generates stickyness in aggregate expectations with important macroeconomic consequences.
Keywords: D84; E31; 330; inflation; expectations; unemployment; monetary policy; Erwartungstheorie; Inflationserwartung; Arbeitslosigkeit; Schätzung; USA